Learning everyday technologies through playful experimenting and cooperative making in pre-primary education - Yliverronen , Virpi; Rönkkö , Marja-Leena; Kangas, Kaiju (FormAkademisk, 2021)
The Finnish National Core Curriculum for pre-primary education (FNBE, 2014) emphasizes the promotion of children’s interests in science and technology, as well as in creative designing and making. The integrative STEAM approach is seen as promising for fostering students’ creative competencies starting from early education stages. In pre-primary education, the STEAM framework has received little research interest; the empirical evidence of its implementation is especially limited. The objective of this present study is to explore pre-primary students’ designing and making processes involving both traditional and digital craft elements, and how their learning of everyday technologies can be supported. The data consists of video recorded sessions, where pre-primary students (n=19, aged 5–6 years) were creating felted “Power Creatures” with soft circuits. The results indicate that with adult and peer student cooperation, pre-primary students are able to create original creatures and use digital elements as a part of their craft product. Playing is endorsed as a learning method to support pre-primary education in both tangible and abstract elements of technology